Development of Debate Text Learning Material with Simulation Method for X Grade Senior High School Students - Amalia Firdausa; Edi Puryanto; Siti Ansoriyah (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aimed to obtain the information about the availability of debate text learning material in school. This research was held in January to June 2020. The main focus in this study was the development of debate text learning material with simulation method for tenth grader of senior high school. The ADDIE model was used as an approach in this research and development (R&D) design. By using debate text learning material with simulation method makes students be able to achieve learning objectives well. Small trial implementation was done on nine X grader of SMK Negeri 40 Jakarta by using the Zoom Meeting and Google Classroom. The result of statistical analysis calculation showed the highest prates score is 70 and the lowest score is 35, while the highest postes score is 95 and the lowest score is 80. Based on the assessment and discussion result by material expert validator and practitioner validator, it was concluded that the debate text material learning material with simulation method for tenth grader of senior high school were proper to be used in the learning process and stimulate students’ skills effectively. Keywords: learning material, debate text, simulation method Abstrak Penelitian ini bertujuan untuk memperoleh informasi tentang ketersediaan materi atau bahan ajar teks debat di sekolah. Penelitian ini dilakukan pada bulan Januari hingga bulan Juni 2020. Fokus penelitian ini adalah pengembangan materi ajar teks debat dengan metode simulasi untuk siswa kelas X SMA/SMK. Penggunaan materi ajar teks debat dengan metode simulasi ini bertujuan untuk membantu siswa mencapai tujuan pembelajaran dengan baik. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan R&D (Research & Development) dengan model ADDIE. Pelaksanaan uji coba terbatas dilakukan pada sembilan orang siswa kelas X SMK Negeri 40 Jakarta melalui aplikasi Zoom Meeting dan Google Classroom. Hasil perhitungan analisis statistik menunjukkan nilai prates tertinggi adalah 70 dan nilai terendah adalah 35, sedangkan nilai postes tertinggi adalah 95 dan nilai terendahnya adalah 80. Berdasarkan hasil penilaian dan diskusi dengan validator ahli materi dan validator praktisi, disimpulkan bahwa produk Pengembangan Materi Ajar Teks Debat dengan Metode Simulasi Siswa Kelas X SMA/SMK layak digunakan dalam proses pembelajaran dan efektif untuk mengasah keterampilan siswa. Kata Kunci: materi ajar, teks debat, metode simulasi